Willful : how we choose what we do - Robb, Richard G., 1960- (Yale University Press, 2019)
A revelatory alternative to the standard economic models of human behavior that proposes an exciting new way to understand decision-making. Why do we do the things we do? The classical view of economics is that we are rational individuals, making decisions with the intention of maximizing our preferences. Behaviorists, on the other hand, see us as relying on mental shortcuts and conforming to preexisting biases. Richard Robb argues that neither explanation accounts for those things that we do for their own sake, and without understanding these sorts of actions, our picture of decision-making is at best incomplete. Robb explains how these choices made seemingly without reason belong to a realm of behavior he identifies as "for-itself." A provocative combination of philosophy and economics that offers a key to many of our quixotic choices, this groundbreaking volume provides a new way to understand everything from how we formulate our desire to work to how we manage daily interactions